Frysseparation av slam och sediment: En studie av Effektivitet och Materialoptimering - Hussein, Redir; Johansson, Victor (My University, 2025)
This report investigates and compares three different methods for sludge drying: passive air drying, active air drying, and freeze separation using Siccum’s technology. The aim was to evaluate each method based on energy consumption, drying efficiency, processing capacity, and potential environmental benefits. The evaluation was conducted through a comparative analysis of each method’s technical and operational performance under controlled conditions. The results show that passive air drying has the lowest energy demand but requires extensive space and time. Active air drying offers faster results at the cost of higher energy usage. Siccum’s freeze separation technology demonstrated the highest energy consumption in the study, but also the greatest ability to process large material volumes through a closed and automated system. Although energy-intensive, freeze separation may be advantageous in large-scale operations where high throughput, controlled processing, and reduced waste volumes are prioritized. The choice of method should be based on specific operational needs, considering factors such as energy costs, available space, processing time, and environmental impact.